Pope Joan Polemic in Early Modern France: The Use and Disabuse of Myth - Tinsley, Barbara Sher (The sixteenth century journal, 1987)
Pope Joan, invented by a thirteenth century monk-chronicler, was believed to have reigned at Rome during the Middle Ages. John Hus said this reign invalidated the papal succession, and later Luther and Calvin followed suit. Many Catholic scholars were also misled. Following the lead of one who was not, Onofrio Panvinio (d. 1568), Florimond de Raemond, a Bordeaux parlementaire, debunked the fable in his popular Erreur Populaire de la Papesse Jane (1587), reprinted fifteen times. Raemond's review of church history was a defence of papal primacy and infallibility. It helped free religious controversy from a dependence on fictitious "evidence," introducing ordinary readers to the problems of historical research.